Answer:
f(-2) = 44
Step-by-step explanation:
Hello there! Lets get started solving this function!
For a function, whenever we see f(x) = ... , the function is simply asking the value of the equation at x! So, if replace f(x) with f(-2), we simply substitute x with -2 in the equation! Lets get started!
![f(x) = -7x + 5x^{2} + 10\\f(-2) = -7(-2) + 5(-2)^{2} + 10\\f(-2) = 14 + 20 + 10\\f(-2) = 44\\](https://tex.z-dn.net/?f=f%28x%29%20%3D%20-7x%20%2B%205x%5E%7B2%7D%20%2B%2010%5C%5Cf%28-2%29%20%3D%20-7%28-2%29%20%2B%205%28-2%29%5E%7B2%7D%20%2B%2010%5C%5Cf%28-2%29%20%3D%2014%20%2B%2020%20%2B%2010%5C%5Cf%28-2%29%20%3D%2044%5C%5C)
First, we can write the original function. Next, we substitute in -2 for x. Then, we find our final terms. Finally, we are given that f(-2) = 44.
Hope this helps! Remember, math is fun!
Answer:
circle
Step-by-step explanation:
circle is a set of all those points in a plane that lie the same distance from a single point in the plane .
I believe the answer is C.
This is rationalising the denominator of an imaginary fraction. We want to remove all i's from the denominator.
To do this, we multiply the fraction by 1. However 1 can be expressed in an infinite number of ways. For example, 1 = 2/2 = 3/3 = 4n^2 / 4n^2 (assuming n is not zero!). Let's express 1 as the complex conjugate of the denominator, divided by the complex conjugate of the denominator.
The complex conjugate of (3 - 2i) is (3 + 2i). Then do what I just said:
4/(3-2i) * (3+2i)/(3+2i) = 4(3+2i)/(3-2i)(3+2i) = (12+8i)/(9-4i^2) = (12+8i)/(9+4) = (12+8i)/13
This is the answer you are looking for. I hope this helps :)
Answer:
9
Step-by-step explanation:
3 x 3 =9 9 divived by 1
9